Doha round of WTO negotiations and the domestic support for agriculture in Serbia - Popović Vesna; Katić Branko (Ekonomski Anali, 2007)
Beside the fact that the green box essential inspection has, obviously, not been carried out, the long expected modality draft in the agricultural sector for July 2006 is full of opposing ponts of view and conflicting solutions to the problem. Thus, the negotiations have been completely suspended, as the very result of the lack of agreement in the field of agriculture (market approach and internal support). It is expected that Doha round of WTO negotiations should result with a significant improvement in reduction of trade distortion support. Serbia is in the process of joining the WTO and is intensively working on meeting the obligations that are expected to be completed in the process; in this case, in the field of internal support to agriculture. .